Research designs and methodological use in Malaysian doctoral research - Cameron, Roslyn (City University Publishing Centre, 2010)
Mixed method research is a growing area of methodological choice for many academics and researchers from across a variety of discipline areas. This chapter provides a brief overview of the rise of mixed methods research, its usage in business and management fields, a discussion on the emergence of mixed methods research designs utilised in the Malaysian context and presents empirical evidence of mixed methods usage in DBA theses undertaken in Malaysia. This will be followed by a discussion of the twelve completed DBA theses.